Aggressive CD4/CD8 Double-Negative Primary Cutaneous T-Cell Lymphoma With Dural Invasion: A Rare Presentation of Mycosis Fungoides?. (January 2021) - Haghayeghi, Koorosh; Robinson-Bostom, Leslie; Olszewski, Adam; Jackson, Cynthia L.; Patel, Nimesh R.; Sewastianik, Tomasz; Carrasco, Ruben D.; Shanmugam, Vignesh; Treaba, Diana O.
Abstract : Abstract: Mycosis fungoides (MF) is primarily characterized by epidermotropic CD3+/CD4+/CD45RO+ memory T cells. CD4/CD8 double-negative MF is an uncommon variant with no presumed prognostic significance. Despite the variability in the clinical course and presentation of MF, most cases behave indolently. About 5% of patients, however, advance to stage IV with visceral organ involvement. Central nervous system metastasis in MF is rare with no known cases of direct central nervous system invasion by MF to date. We report an exceedingly rare locally aggressive case of CD4/CD8 double-negative MF with direct dural invasion and underline pertinent diagnostic challenges encountered in our case.